Water pH and the Effectiveness of Pesticides - Frederick M. Fishel; Jason A. Ferrell (EDIS)
PI-156, a 3-page fact sheet by F. M. Fishel and J. A. Ferrell, discusses the effects of alkalinity and presents some methods for preventing this reaction in pesticide mixes. Includes references. Published by the UF Pesticide Information Office, June 2007.